Executive attention training effects in children aged 4 and 6 years: improvement in the trained task greater for 6-year-olds, but far transfer greater for 4-year-olds - Deja, Monika; Zając-Lamparska, Ludmiła; Trempała, Janusz (Frontiers in Public Health, 2025)
In recent years, research on the effectiveness of cognitive training has become increasingly popular. These studies are conducted across all age groups, including both typically developing individuals and those from clinical populations. However, their results remain inconclusive. The purpose of the present study was to verify the effectiveness of executive attention (EA) training for children in the period of middle childhood and of the transfer of the training effects onto non-trained tasks engaging working memory (WM) and fluid intelligence (Gf). The sample consisted of 180 typically developing children from two age groups: 4- and 6-year-olds. The children were divided into three research groups: the Training Group (EA training, 14 sessions), the Active Control Group (naming objects, 14 sessions), and the Passive Control Group (lack of activity). In the Training Group, the computer version of the adaptive EA training was used. WM and Gf were assessed in each group in the pre-test and post-test. The obtained data indicate the existence of asymmetry in the scope of training effects. EA training leads to a higher improvement in the correctness of performing tasks in 6-year-old children than in 4-year-old children (F = 11.603; p < 0.001; η2p = 0.167). On the other hand, the transfer effect on Gf is greater in the group of 4-year-olds compared to 6-year-olds (F = 4.278; p = 0.015; η2p = 0.047), and the scope of transfer to WM is the same in both age groups (F = 0.772; p = 0.464; η2p = 0.009). The obtained results indicate the effectiveness of executive attention training in children in these age groups. The results suggest that older children benefit more from practicing specific cognitive skills. In comparison, the far transfer mechanisms of training effects seem stronger in younger children.